What is God like? - Evans, Rachel Held, 1981-2019; Turner, Matthew Paul, 1973- (Convergent Books, 2021)
"Children who are introduced to God, through attending church or having loved ones who speak often about God, often have a lot of questions, including this ever-popular one: What is God like? The late Rachel Held Evans loved the Bible and loved showing God's love through the words and pictures found in that ancient text. Through these pictures from the Bible, children see that God is like a shepherd, God is like a star, God is like a gardener, God is like the wind, and more. God is a comforter and support"--